High-Performance Near-Infrared Photodetector Based on PbS Colloidal Quantum Dots/ZnO-Nanowires Hybrid Nanostructures - Vincent Teng (Sensors, 2023)
Quantum dots have found significant applications in photoelectric detectors due to their unique electronic and optical properties, such as tunable bandgap. Recently, colloidal quantum dots (CQDs) have attracted much interest because of the ease of controlling the dot size and low production cost. In this paper, a high-performance ZnO/PbS heterojunction photodetector was fabricated by spin-coating PbS CQDs onto the surface of a hydrothermally grown vertical array of ZnO nanowires (NWs) on an indium tin oxide (ITO) substrate. Under 940 nm near-infrared light illumination, the device demonstrated a responsivity and detectivity of ~3.9 × 104 A/W and ~9.4 × 1013 Jones, respectively. The excellent performances and low cost of this nanocomposite-based photodetector show that it has the potential for widespread applications ranging from medical diagnosis to environmental monitoring.